Using Combined Accrual and Cash Ratio Analysis to Determine Pre-Bankruptcy Status - Alexey Litvinenko (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Questions- 1) To what extent does the combined use of accrual-based and cash-based ratio analysis provide comprehensive insights into a company's solvency, liquidity, profitability and efficiency? 2) Does the combined accrual-based and cash-based ratio analysis help in revealing manipulations in accrual financial statements? 3) How does the analysis of profitability and efficiency explain the results and levels of solvency and liquidity in a company? Do solvency and liquidity depend on external or internal sources of financing? 4) Does the present method of analysis indicate which company is closer to the pre-bankruptcy stage? Motivation- despite high demand from business practice and academics, there are not enough literature and methods combining cash-based and accrual-based ratio analyses in the specific dimensions of solvency, liquidity, profitability and efficiency for the determination of the pre-bankruptcy state of production companies. Idea- in this paper, the author created a method of analysis combining cash-based and accrual-based ratios in four dimensions (solvency, liquidity, profitability and efficiency) for the determination of the pre-bankruptcy state of production companies. Data- historical panel data for the years 2013-2022 obtained from the annual, managerial, and auditor's reports of two production companies listed on the Baltic Stock Exchange. Tools- The mixed methods were used combining quantitative ratio calculations based on the historical panel data from financial statements with qualitative explanatory information from financial reports. Findings- The developed combination of ratio counterparts proves to be highly informative. The ratios used across all dimensions complement each other, providing a comprehensive picture of the companies' financial positions. Discrepancies within the ratio pairs suggest possible manipulations in accrual-based ratios. Low profitability and efficiency results during the first five years of analysis predicted a subsequent decrease in solvency and liquidity. Maintaining high levels of profitability and efficiency, and avoiding reliance on debt is crucial to sustain solvency and liquidity. A company is closer to pre-bankruptcy if the ratio analysis reveals significant discrepancies between the counterparts, with negative results prevailing. Contribution- the paper contributes to both business practice (accountants, auditors, financial managers) and the ongoing academic discussion with the dual method of ratio analysis for a more precise determination of the pre-bankruptcy state of the companies. This method allows to determine manipulations in accrual-based financial statements more effectively.
Keywords: M41; M42; 650; cash flow ratios analysis; accrual-based ratios analysis; solvency analysis; liquidity analysis; profitability analysis; efficiency analysis